Development of mass spectrometric tools for the structural characterization of glycosphingolipids in parasitic samples - Luh, David; Justus Liebig University Giessen (My University, 2025)
In this dissertation, the analyses of glycosphingolipids (GSLs) in parasitic samples was addressed. For this, the combination of mass spectrometry imaging (MSI) and nano liquid chromatography mass spectrometry (nano-LC MS) data yielded an overview about GSLs on a molecular level in parasitic samples. Especially the MSI data for each model system, which was investigated, were necessary to pinpoint possible functions of GSLs. In a first project, Schistosoma (S.) mansoni-infected hamsters were selected as a model system for schistosomiasis. Here, the incorporation of S. mansoni eggs in the liver of the hamster provokes an immune response, leading to granuloma formation, which is the main cause of chronic pathogenesis. For the bulk-analysis, experimental parameters such as the extraction and purification of GSLs and the nano-LC MS analysis, were optimized. The statistical data analysis revealed a significant upregulation of GSL species compared to control groups. To associate different GSL species more specifically to the host-parasite interaction, MSI experiments were performed. But first, the matrix application of 2,5-dihydroxyacetophenone was optimized for high-resolution MSI down to 3 µm step size. With the MSI workflow, GSL species were unambiguously localized within granulomas. Even substructures within the granulomas and the S. mansoni eggs were revealed. There are strong indications that observed distributions of specific GSL species matched immune cells, which are subsequently recruited during the immune response. In addition, a semi-quantitative evaluation of MALDI MSI data is proposed. The evaluation is in-line with the semi-quantitative data analysis of the nano-LC MS experiments, demonstrating that the MSI methodology is suitable for qualitative and semi-quantitative analyses. In the second project, the GSLs during a Fasciola hepatica infection were in focus. First, the nano-LC MS method was validated for isolated adult F. hepatica through comparison with the literature. Besides already reported GSL species, we were able to identify previously unknown GSL species for F. hepatica. Further, we analysed the acute and chronic infection stage of rats, infected with F. hepatica. For this, a semi-automatic data analysis was established, reducing the analysis time of the nano-LC MS data drastically. To study the host-parasite interaction in more depth, MSI experiments were performed with liver of rats during the acute infection stage. Here, the immature F. hepatica is migrating through the liver parenchyma, causing severe damage to the host. Again, distributions of specific GSL species were correlated to potential immune cell distributions. This is also true for other lipid classes, which were simultaneously detected during the MSI experiments. Furthermore, MSI experiments of isolated F. hepatica may help to better understand the metabolism of GSL species. The comparison to immature F. hepatica also revealed variations in GSL distributions and contributes to a better understanding of the development of F. hepatica. Overall, the developed method allows researchers to structurally and locally study the GSL profile in parasitic samples. The method is also applicable for other sample systems. Additionally, to further improve the sensitivity for GSL detection in MSI experiments, which is a perquisite for on-tissue tandem MS experiments, salt doping MSI experiments were performed with isolated adult F. hepatica. Compared to normal MSI experiments, an increased number of GSL distributions were revealed, providing a promising outlook to further extended studies on GSLs.
Keywords: MALDI MSI; nano-LC; Schistosoma mansoni; Fasciola hepatica; Glycosphingolipids; ddc:540